Investigating Factors of False-Positive Results of Aspergillus Galactomannan Assay: A Case–Control Study in Intensive Care Units - Hung, Yu-Hsuan; Lai, Hui-Hsiung; Lin, Hui-Chuan; Sun, Kuo-Shao; Chen, Chung-Yu (Frontiers in Pharmacology, 2021)
Background: Relevance between false-positive galactomannan (GM) enzyme immunoassay (EIA) results and treatment for critically ill patients are scarce. Objectives: The study aimed to determine the false-positive rate of GM-EIA and to probe the risk factors of false positivity among patients in the intensive care units (ICU). Methods: A case-control approach was conducted to retrospect adult patients who had at least one GM-EIA result and were admitted to the ICU. Those who had no fungus culture were excluded. The clinical characteristics and critical care between patients with false-positive and true-negative GM index (GMI) were compared. Results: Of 206 patients enrolled and with GM-EIA result, 20 (9.7%) were considered to have false-positive antigenemia, including 9 in BALs and 11 in serum. 148 (71.8%) were true-negatives. After paired grouping of 1:4, factors researched in the previous studies showed no significant difference. However, compared with the true-negatives, patients with positive GM test results but were incompatible with the diagnosis of invasive aspergillosis were more prone to the risk of false positivity, with the use of colistin inhalation. It seemed to be the only factor that significantly increased the risk of false positivity after multivariate analysis. (Adjusted odds ratio, 35.68; 95% confidence interval, 3.77-337.51, p = 0.002). Conclusions: Colistin inhalation treatment may contribute to false-positive GM-EIA results. The positive GM index among patients receiving colistin nebulization should be interpreted with caution.